Climate change drives habitat contraction of a nocturnal arboreal marsupial at its physiological limits. Issue 10 (8th October 2020) - Wagner, Benjamin; Baker, Patrick J.; Stewart, Stephen B.; Lumsden, Linda F.; Nelson, Jenny L.; Cripps, Jemma K.; Durkin, Louise K.; Scroggie, Michael P.; Nitschke, Craig R.
Abstract: Increasing impacts of climatic change and anthropogenic disturbances on natural ecosystems are leading to population declines or extinctions of many species worldwide. In Australia, recent climatic change has caused population declines in some native fauna. The projected increase in mean annual temperature by up to 4°C by the end of the 21st century is expected to exacerbate these trends. The greater glider ( Petauroides volans ), Australia's largest gliding marsupial, is widely distributed along the eastern coast, but has recently experienced drastic declines in population numbers. Its association with hollow‐bearing trees, used for nesting, has made it an important species for the conservation of old‐growth forest ecosystems. Fires and timber harvesting have been identified as threats to the species. Greater gliders have disappeared however from areas that have experienced neither raising questions about the role of other factors in their decline. A unique physiology and strict Eucalyptus diet make them vulnerable to high temperatures and low water availability. As such, climatic conditions may drive habitat selection and recent climatic trends may be contributing to observed population declines. Using presence:absence data from across its distribution in Victoria, coupled with high spatial and temporal resolution climatic data and machine‐learning modeling, we tested the influence of climatic, topographic, edaphic, biotic, and disturbance variables on greater glider occupancy and habitat suitability. We found that climatic variables, particularly those related to aridity and extreme weather conditions, such as number of nights warmer than 20°C, were highly significant predictors of greater glider occurrence. Climatic conditions associated with habitat suitability have changed over time, with increasing aridity across much of its southeastern distribution. These changes in climate are closely aligned with observed population declines across this region. At higher elevation, some areas where the greater glider is observed at high densities, conditions have become wetter, which is improving habitat quality. These areas are of growing significance to greater glider conservation as they will become increasingly important as climatic refugia in the coming decades. Protecting these areas of habitat will be critical for facilitating the conservation of greater gliders as the broader landscape becomes less hospitable under future climatic change.